Effect of hydroponic horse gram fodder and hydroponic sun hemp fodder with replacement of concentrate mixture on the post weaning growth performance of Tellicherry kids - JEMIMAH, E RACHEL; GNANARAJ, P TENSIGH; MUTHURAMALINGAM, T; DEVI, T; BHARATHIDASAN, A (The Indian Journal of Animal Sciences, 2017)
Different seeds such as barley, wheat and yellow maize were utilized for fodder production by hydroponic method. However, this novel experiment was aimed to study the effect of hydroponic horse gram fodder and hydroponic sun hemp fodder with 50% replacement of concentrate mixture on the growth performance in Tellicherry kids. Sixty male Tellicherry kids at the age of 3 months were randomly divided into 3 groups each having 20 kids’ viz. treatment 1 (100% concentrate), treatment 2 (50% concentrate + hydroponic horse gram fodder) and treatment 3 (50% concentrate + hydroponic sun hemp fodder). Palatability trial was conducted for a period of 7 days to assess the maximum intake of hydroponic fodders by the kids. After analyzing the palatability and chemical composition, feeding trial was formulated on as fed basis. Duration of the study was 30 days. Production parameters such as total body weight gain (kg), daily body weight gain (kg), total feed intake/head/30 day (kg) (DM basis) and feed conversion efficiency (%) and cost of feeding were studied. After analysis of collected data, no significant difference was noticed between the groups in terms of total body weight gain, daily body weight gain, total feed intake/head/30 day on DM basis and feed conversion efficiency. Cost of feeding/animal was lower in sun hemp fodder fed groups. Thus, hydroponic horse gram fodder and sun hemp fodder can be used as an alternative for concentrate mixture in the feed ration of Tellicherry kids.